The kinetic energy of PAH dication and trication dissociation determined by recoil-frame covariance map imaging. Issue 38 (25th July 2022) - Lee, Jason W. L.; Tikhonov, Denis S.; Allum, Felix; Boll, Rebecca; Chopra, Pragya; Erk, Benjamin; Gruet, Sebastian; He, Lanhai; Heathcote, David; Kazemi, Mehdi M.; Lahl, Jan; Lemmens, Alexander K.; et al.
Abstract : The kinetic energy of dissociation of polycyclic aromatic hydrocarbons is determined by application of recoil-frame covariance imaging analysis to velocity map images. Abstract : We investigated the dissociation of dications and trications of three polycyclic aromatic hydrocarbons (PAHs), fluorene, phenanthrene, and pyrene. PAHs are a family of molecules ubiquitous in space and involved in much of the chemistry of the interstellar medium. In our experiments, ions are formed by interaction with 30.3 nm extreme ultraviolet (XUV) photons, and their velocity map images are recorded using a PImMS2 multi-mass imaging sensor. Application of recoil-frame covariance analysis allows the total kinetic energy release (TKER) associated with multiple fragmentation channels to be determined to high precision, ranging 1.94–2.60 eV and 2.95–5.29 eV for the dications and trications, respectively. Experimental measurements are supported by Born–Oppenheimer molecular dynamics (BOMD) simulations.